Neoliberalism and political theology from Kant to identity politics - Raschke, Carl A. (Edinburgh University Press, 2019)
Shatters the common academic myth that neoliberalism is simply free market fundamentalism plus political conservatism. Neoliberalism in recent years has become the operative buzzword among pundits and academics to characterise an increasingly dysfunctional global political economy. It is often--wrongly--identified exclusively with free market fundamentalism and illiberal types of cultural conservatism. Combining penetrating argument and broad-ranging scholarship, Carl Raschke shows what the term really means, how it evolved and why it has been so misunderstood. Raschke lays out how the present new world disorder, signalled by the election of Trump and Brexit, derives less from the ascendancy of reactionary forces and more from the implosion of the post-Cold War effort to establish a progressive international moral and political order for the cynical benefit of a new cosmopolitan knowledge class, mimicking the so-called civilising mission of 19th-century European colonialists.--